Cost-effectiveness of low-level laser therapy (LLLT) in head and neck cancer patients receiving concurrent chemoradiation. (January 2016) - Antunes, Héliton S.; Schluckebier, Luciene Fontes; Herchenhorn, Daniel; Small, Isabele A.; Araújo, Carlos M.M.; Viégas, Celia Maria Pais; Rampini, Mariana P.; Ferreira, Elza M.S.; Dias, Fernando L.; Teich, Vanessa; Teich, Nelson; Ferreira, Carlos G.
Highlights: We are the first to investigate the impact of LLLT on the cost of treatment those patients. We report data suggesting that morbidity was lower in the Laser Group. The incremental cost-effectiveness ratio (ICER) was US$ 4961.37 per grade 3–4 OM case prevented compared to no treatment. LLLT was more cost-effective than placebo. Summary: Background: Oral mucositis is a major event increasing treatment costs of head and neck squamous cell carcinoma (HNSCC) patients treated with chemoradiation (CRT). This study was designed to estimate the cost-effectiveness of low-level laser therapy (LLLT) to prevent oral mucositis in HNSCC patients receiving CRT. Methods: From June 2007 to December 2010, 94 patients with HNSCC of nasopharynx, oropharynx, and hypopharynx entered a prospective, randomized, double blind, placebo-controlled, phase III trial. CRT consisted of conventional radiotherapy (RT: 70.2 Gy, 1.8 Gy/d, 5 times/wk) + concurrent cisplatin (100 mg/m 2 ) every 3 weeks. An InGaAlP (660 nm–100 mW–4 J/cm 2 ) laser diode was used for LLLT. Results: From the perspective of Brazil's public health care system (SUS), total costs were higher in Placebo Group (PG) than Laser Group (LG) for opioid use (LG = US$ 9.08, PG = US$ 44.28), gastrostomy feeding (LG = US$ 50.50, PG = US$ 129.86), and hospitalization (PG = US$ 77.03). In LG, the cost was higher for laser therapy only (US$ 1880.57). The total incremental cost associated with the use of LLLT was US$ 1689.00 per patient. The incremental cost-effectiveness ratio (ICER) was US$ 4961.37 per grade 3–4 OM case prevented compared to no treatment. Conclusions: Our results indicate that morbidity was lower in the Laser Group and that LLLT was more cost-effective than placebo up to a threshold of at least US$ 5000 per mucositis case prevented. Clinical trial information: NCT01439724.